Comprehensive real-time metabolic profiling of peripheral blood mononuclear cells reveals important methodological considerations for immunometabolism research - Macleod, Michael; Pradana, Fendi; Wadley, Alex J.; Barlow, Jonathan (Frontiers in Immunology, 2025)
Background/IntroductionThe utility of measuring real-time cellular bioenergetics of peripheral blood mononuclear cells (PBMCs) as biomarkers in disease monitoring, such as the bioenergetic health index, is of emerging interest. However, various experimental factors can impact the accuracy and reproducibility of these measurements.Methods: PBMC bioenergetics were probed in real-time using extracellular flux analysis to identify optimal seeding density and injection protocol. Using a modified protocol, we assessed the extent to which blood processing time and isolation method (SepMate™ vs. EasySep™ Direct) influence PBMC bioenergetics under basal and stimulated conditions. Advanced metabolic control analysis including mitochondrial and glycolytic ATP supply flux, respiratory control ratio, bioenergetic health index, and mitochondrial toxicity index were used to identify and quantify PBMC bioenergetics.ResultsMeasures of metabolic profiling such as mitochondrial respiration, glycolytic activity, ATP supply flux, and respiratory control ratio were significantly diminished in PBMCs due to blood processing delay (48–72 hours) and were influenced by isolation method. Extended blood processing time significantly lowered T cell activation capacity in PBMCs, evidenced by decreased responses of mitochondrial and glycolytic ATP supply to CD3/CD28 activation.Discussion/ConclusionThis study demonstrates that key experimental variables including blood processing time and isolation method critically affect the reliability and biological relevance of PBMC metabolic assessments, highlighting the importance of protocol standardisation for accurate bioenergetic biomarker measurements.